Physical Activity Determinants in Older People: An Analysis of the UK Understanding Society Wave 2. (20th October 2021) - Ikpeme, M; Pang, D
Abstract: Background: Ageing leads to inactivity and conditions like heart disease, type II diabetes, and risk of falls. Regular physical activity (PA) helps with a renewed feeling of ability, efficient blood circulation, balance, and coordination. In the UK, physical inactivity is the fourth largest killer of the elderly. This study examines some physical activity determinants in older people. Methods: A cross-sectional analysis of the UKUS cohort study Wave 2 (2010-12) with participants aged 65 and above was done. The descriptive analyses involved crosstabulations and pictorials in SPSS and Microsoft Office. Data was dichotomised for 2x2 tables in OpenEpi for the univariate analyses. Multivariate analysis was via ordinal logistic regression in SPSS. As Wave 2 had no variable describing PA, a 'total physical activity' (TPA) score was created. TPA is composed of the addition of the total walking score (TWS), total hobbies/sports score (THSS), 'total physicality score' (TPS), and total sport frequency (TSF). All five variants were created by indexing available proxy variables unique to each category. Results were reported with odds ratios and 95% confidence intervals. Results: Univariate analysis with TPA showed an association with some variables like income, OR = 15.25 (8.57-27.12), social interaction, OR = 2.11 (1.46-3.05), family interaction, OR = 2.69(1.45-4.98), wellbeing, OR = 312(157.5-617.9), physical health, OR = 2.84(1.39-5.81) and emotional health, OR = 2.42(1.21-5.07). Multivariable analysis after adjusting for age and sex yielded no significant associations between most PA and predictors. Some significant associations include TWS and social class, AOR= 2.59 (P = 0.013), green food consumption, and TPS, AOR= 1.47 (P < 0.05). Conclusions: In general, higher income, gross personal income, social class, wellbeing, and green food consumption seemed to produce greater odds of participating in all physical activities. Key messages: These findings suggest the need for other social determinants to be thoroughly investigated. There is also a need for older adults to be well provided for so these determinants of health can improve their quality of life.